2015
DOI: 10.1186/s12933-015-0299-8
|View full text |Cite
|
Sign up to set email alerts
|

SIRT1 protects against myocardial ischemia–reperfusion injury via activating eNOS in diabetic rats

Abstract: BackgroundDiabetic patients are more sensitive to myocardial ischemic injury than non-diabetic patients. Silent information regulator 1 (SIRT1) is a nicotinamide adenine dinucleotide-dependent histone deacetylase making the heart more resistant to ischemic injury. As SIRT1 expression is considered to be reduced in diabetic heart, we therefore hypothesized that up-regulation of SIRT1 in the diabetic heart may overcome its increased susceptibility to ischemic injury.MethodsMale Sprague–Dawley rats were fed with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
84
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(89 citation statements)
references
References 49 publications
5
84
0
Order By: Relevance
“…Delivery of adenoviral vectors encoding SIRT1 into the hearts of diabetic rats markedly increased SIRT1 expression and was accompanied by a reduced cardiomyocyte apoptosis, superoxide generation, and by a simultaneous eNOS activation (46). SIRT1 protects blood vessels from hyperglycemiainduced endothelial dysfunction through a mechanism involving the downregulation of p66…”
Section: Sirtuins and Altered Glucose Homeostasismentioning
confidence: 99%
“…Delivery of adenoviral vectors encoding SIRT1 into the hearts of diabetic rats markedly increased SIRT1 expression and was accompanied by a reduced cardiomyocyte apoptosis, superoxide generation, and by a simultaneous eNOS activation (46). SIRT1 protects blood vessels from hyperglycemiainduced endothelial dysfunction through a mechanism involving the downregulation of p66…”
Section: Sirtuins and Altered Glucose Homeostasismentioning
confidence: 99%
“…Collectively, our results suggested that SIRT1 may prove to be an important therapeutic target for the treatment of CIRI. Ding et al also suggested that SIRT1 protected against myocardial ischemia-reperfusion injury in diabetic rats (23).…”
Section: Discussionmentioning
confidence: 99%
“…The LAD artery was retied after the 6 h of reperfusion and myocardial infarct size (INF) was evaluated by Evans Blue/triphenyltetrazolium chloride (TTC) staining as we described before (Ding et al, 2015). Evans blue (2%) was perfused through the aorta to stain the myocardial area not at risk.…”
Section: Determination Of Myocardial Infarct Sizementioning
confidence: 99%
“…Superoxide generation in heart tissue was determined as we described previously (Ding et al, 2015) by lucigenin-enhanced chemiluminescence. The results were indicated as relative light units (RLU) per milligram dry weight per second (RLU/mg/s).…”
Section: Quantification Of Superoxide Generation Malonaldialdehyde (mentioning
confidence: 99%